Language in mind : advances in the study of language and thought - Gentner, Dedre; Goldin-Meadow, Susan (MIT Press, 2003)
The idea that the language we speak influences the way we think has evoked perennial fascination and intense controversy. According to the strong version of this hypothesis, called the Sapir-Whorf hypothesis after the American linguists who propounded it, languages vary in their semantic partitioning of the world, and the structure of one's language influences how one understands the world. Thus speakers of different languages perceive the world differently. Although the last two decades have been marked by extreme skepticism concerning the possible effects of language on thought, recent theoretical and methodological advances in cognitive science have given the question new life. Research in linguistics and linguistic anthropology has revealed striking differences in cross-linguistic semantic patterns, and cognitive psychology has developed subtle techniques for studying how people represent and remember experience. It is now possible to test predictions about how a given language influences the thinking of its speakers. Language in Mind includes contributions from both skeptics and believers and from a range of fields. It contains work in cognitive psychology, cognitive development, linguistics, anthropology, and animal cognition. The topics discussed include space, number, motion, gender, theory of mind, thematic roles, and the ontological distinction between objects and substances. ContributorsMelissa Bowerman, Eve Clark, Jill de Villiers, Peter de Villiers, Giyoo Hatano, Stan Kuczaj, Barbara Landau, Stephen Levinson, John Lucy, Barbara Malt, Dan Slobin, Steven Sloman, Elizabeth Spelke, and Michael Tomasello